Teacher’s Training for Educational Quality Teaching - Andrea Alliaud (Education Policy Analysis Archives, 2014)
In the last thirty years the issue of educational quality has crossed the political agenda. The existence of a relationship between improving education systems and teacher training was the assumption that motorized numerous interventions in the areas of vocational training, both initial and continuing. Still, we can distinguish two reform movements in the country and in the region: one, in the 1990s, which partnered quality with efficiency of the education systems, and one in the 2000s, which understands education quality as social justice. In this article, we intend to show that if quality is exclusively seen from a performance perspective, which would be achieved by the definition of “external parameters”, ignoring the knowledge and practices of the subjects, is neither efficient nor fair. We also argue that, more than policies that “humiliate the craft” of teaching we need working and training conditions that strengthen the craft. As we are convinced that quality education is essential for achieving educational systems and fairer societies, we advocate for practices and policies that incorporate the knowledge and practice of the various parties involved in the transmission process.